Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the system of equations using the substitution method, we will follow these steps:
1. Express [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex] using the first equation:
[tex]\( x + 2y = 1 \)[/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ x = 1 - 2y \][/tex]
2. Substitute [tex]\( x = 1 - 2y \)[/tex] into the second equation:
The second equation is [tex]\( 5x + 3y = -23 \)[/tex]. Substitute [tex]\( x \)[/tex]:
[tex]\[ 5(1 - 2y) + 3y = -23 \][/tex]
3. Simplify and solve for [tex]\( y \)[/tex]:
[tex]\[ 5 \cdot 1 - 5 \cdot 2y + 3y = -23 \][/tex]
[tex]\[ 5 - 10y + 3y = -23 \][/tex]
[tex]\[ 5 - 7y = -23 \][/tex]
Subtract 5 from both sides:
[tex]\[ -7y = -23 - 5 \][/tex]
[tex]\[ -7y = -28 \][/tex]
Divide both sides by -7:
[tex]\[ y = \frac{-28}{-7} \][/tex]
[tex]\[ y = 4 \][/tex]
4. Substitute [tex]\( y = 4 \)[/tex] back into the expression for [tex]\( x \)[/tex]:
[tex]\[ x = 1 - 2y \][/tex]
[tex]\[ x = 1 - 2 \cdot 4 \][/tex]
[tex]\[ x = 1 - 8 \][/tex]
[tex]\[ x = -7 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ (x, y) = (-7, 4) \][/tex]
1. Express [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex] using the first equation:
[tex]\( x + 2y = 1 \)[/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ x = 1 - 2y \][/tex]
2. Substitute [tex]\( x = 1 - 2y \)[/tex] into the second equation:
The second equation is [tex]\( 5x + 3y = -23 \)[/tex]. Substitute [tex]\( x \)[/tex]:
[tex]\[ 5(1 - 2y) + 3y = -23 \][/tex]
3. Simplify and solve for [tex]\( y \)[/tex]:
[tex]\[ 5 \cdot 1 - 5 \cdot 2y + 3y = -23 \][/tex]
[tex]\[ 5 - 10y + 3y = -23 \][/tex]
[tex]\[ 5 - 7y = -23 \][/tex]
Subtract 5 from both sides:
[tex]\[ -7y = -23 - 5 \][/tex]
[tex]\[ -7y = -28 \][/tex]
Divide both sides by -7:
[tex]\[ y = \frac{-28}{-7} \][/tex]
[tex]\[ y = 4 \][/tex]
4. Substitute [tex]\( y = 4 \)[/tex] back into the expression for [tex]\( x \)[/tex]:
[tex]\[ x = 1 - 2y \][/tex]
[tex]\[ x = 1 - 2 \cdot 4 \][/tex]
[tex]\[ x = 1 - 8 \][/tex]
[tex]\[ x = -7 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ (x, y) = (-7, 4) \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.